Perception of the network in the African context through the narratives of the women involved in three networks in Togo - (:unkn) unknown (My University, 2024)
Although there are several studies on women’s networks in Africa, very few of them address the question of how women perceive the concept of network. Through a qualitative research based on observations and semi-structured interviews conducted in Togo with eighteen women belonging to three different networks (women entrepreneurs, women employees and women activists for women’s self-promotion), this research focuses on the respondents’ in-depth understanding of the concept of a network. The perception of the network seems to be specific to the African context, and particularly to Togo, and appears to differ from that observed in the literature. Using Miles and Huberman’s (1991) matrix analysis technique, a new light is shed on the purposes of a network, perceived through eight levels of contribution: support, learning, social impact, career development, manifestation of religion, affinity, challenge and family relationship. Certain levels of understanding, including the perception of the network as a manifestation of religion as well as a social impact, are new. The discussion also proposes that women’s networks in Togo constitute an explicit or implicit means of emancipation and empowerment for African women.
Keywords: African Research